2013
DOI: 10.1159/000350498
|View full text |Cite
|
Sign up to set email alerts
|

Management of Elderly Patients with Advanced Non-Small Cell Lung Cancer: A Single-Center Experience

Abstract: Background: Optimal management of elderly patients (≥70 years) with non-small cell lung cancer (NSCLC) remains debatable. We compared survival and treatment of advanced NSCLC between elderly and younger patients. Methods: From the cancer registry, we identified 188 patients treated with chemotherapy for stage IV NSCLC. Patient characteristics, survival, toxicity, chemotherapy regimen and response were compared between age groups (patients 50-69 vs. ≥70 years). Results: There were 96 young and 92 elderly patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…For those patients with locally advanced (stage IIIB) or metastatic (stage IV) disease and with a good functional status, chemotherapy-based treatment generally consists of platinum-based combinations, achieving a modest survival benefit compared to platinum-free regimens [4,5]. Platinum doublets, such as pemetrexed, gemcitabine, or taxane plus platinum combinations, have comparable efficacies [6].…”
Section: Introductionmentioning
confidence: 99%
“…For those patients with locally advanced (stage IIIB) or metastatic (stage IV) disease and with a good functional status, chemotherapy-based treatment generally consists of platinum-based combinations, achieving a modest survival benefit compared to platinum-free regimens [4,5]. Platinum doublets, such as pemetrexed, gemcitabine, or taxane plus platinum combinations, have comparable efficacies [6].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with lung cancer, OS is significantly shorter for patients with ≥5% weight loss than for those with <5% weight loss [3,4]. Früh et al [5] reported that age was not associated with weight loss. In patients with early-stage lung cancer, surgery is usually performed.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rate of NSCLC increases gradually with age, and the median age of patients diagnosed with NSCLC is 71 years [2]. Nevertheless, few trials for the chemotherapy of advanced NSCLC have been performed in elderly patients because of the physiological decline of organ functioning, the exhausted functional reserve and the higher possibility of concomitant diseases [3,4]. …”
Section: Introductionmentioning
confidence: 99%